The Scope of Legal Protection of a Utility Model - Evgenievich Kitaiskiy, Vladimir; Sabirzhanovich Moukhamedshin, Irik; Nikolaevich Petrov, Evgeniy; Ivanovna Tytskaya, Galina (International Journal of Engineering and Technology, 2018)
As is known, the scope of legal protection of a utility model is determined by its formula. The utility model formula should clearly express the essence of the utility model, which is determined by a set of essential characteristics sufficient to solve the technical problem and obtain a given technical result. However, often the authors of a patent application include in the utility model formula not merely a set of essential characteristics but also other characteristics that are not required to solve the technical problem and to achieve the technical result, indicated by the applicant. Such nonessential characteristics are superfluous, reducing the scope of legal protection of the patented utility model. The utility models, containing the insignificant characteristics in the formula, which restrict the rights of the patentees to protect their rights in case of unauthorized use of the utility model, are considered in this article. The results of the study are illustrated by the specific example from judicial practice.Â